NILAI- NILAI PENDIDIKAN KARAKTER DALAM NOVEL 172 DAYS KARYA NADZIRA SHAFA SERTA RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Siti Nurawaliyah; Susilawati; H. Syafiudin (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The influence of globalization and the rapid sophistication of information and communication technology, it turns out, has added new problems to the world of education, and the most crucial is the problem of student character. In this study, the value of character education is the focus of the study because currently the value of character education is in the spotlight which is often associated with the rampant deviant behavior carried out by students. The purpose of this study is to describe the values ​​of character education contained in the novel 172 Days by Nadzira Shafa and to describe the relevance of the values ​​of character education contained in the novel 172 Days with Indonesian language learning in high school. This study uses a qualitative approach and a type of library research. The data collection technique uses document analysis. The data analysis technique used is the content analysis technique. The results of this study indicate that: The novel 172 Days by Nadzra Shafa contains 11 values ​​of character education which include religious, responsible, honest, hard work, discipline, creative, independent, curious, fond of reading, social care and friendly/communicative. The relevance of character education values ​​in the novel 172 Days by Nadzira Shafa to Indonesian language learning is found in Indonesian language learning in high school class XI with prose text learning materials on elements, reading and viewing the independent curriculum. Reviewed based on aspects of language, psychology, and cultural background, the novel 172 Days by Nadzira Shafa which contains character education values ​​is worthy of being used as a literary teaching material in high school.